Compartimentação geossistêmica do campo dunar da planície costeira do município de Estância - Sergipe - Prata, Marçal Lukas Martins (2021)
The coastal zone is an area characterized by multiple uses and increasing occupation by human societies. Such conditions contribute to the emergence of environmental problems, often due to the lack of a thorough assessment of the potential and limitations of the landscape components. The coastal plain of Estância is in this context, characterized by a set of morphologies, where the dune field is composed of mobile, semi-fixed and fixed dunes. The goal of this study is to compartmentalize the dune field of the Estancia coastal plain according to geosystemic assumptions. For this, the systemic analysis outlined in the theoretical model of Bertrand (2004) was adopted, whose tripod - ecological potential, biological exploration and anthropic action, allows the integrated analysis of the landscape. In the Dune Field Geosystem, Geofaces were identified - Active Primary Dunes, Active Secondary Dunes and Inactive Pleistocene Dunes. The compartments were named based in classifications by Sloss; Sheperd; Hesp's (2012) and Giannini et al. (2005). Among the methodological procedures used are bibliographic and documentary research, fieldwork and analysis of satellite images. The Active Primary Dunes Geofaces are characterized by the dynamics linked to the beach system and suffer interference from oceanic processes. It is composed of low altitude dunes, such as shadow dunes and nebkhas, colonized by herbaceous restinga. In this compartment the morphodynamics is strong, inherent to the stage Resistasy with Natural and Antropical Geomorphogenesis. The Active Secondary Dunes Geofaces gathers features that evolved from the Active Primary Dunes, but that acquired greater height, length and width. It contains barcan dunes and residual dunes occupied by shrub and / or arboreal restinga, which partially controls the intensity of morphodynamics, which varies from medium to strong. This unit reflects the evolutionary stage in Associated Mosaic of Biostasy and Resistasy. The Geofacies DInactive Pleistocene Dunes is located away from the coast line and presents mainly modeled with shrub/arboreal restinga. In general, the action of wind processes is reduced and the morphodynamics is weak. Such attributes confirm the stage of Biostasy with Regressive Dynamics. Although the Geofacies of the Dune Field Geosystem configure a dynamic of interdependence, they have specificities. The use and occupation of the land contributes so that these compartments are subject to problems related to the loss of biodiversity, coastal erosion and reactivation of the wind process, which have repercussions in the environmental and social context.